Jangles : a big fish story - Shannon, David, 1959- (New York : Blue Sky Press, 2012)
A father relates to his son the tale of his encounter--and friendship--with a gigantic trout whose enormous jaw is covered with so many lures and fish hooks that he jangles when he swims, but who has never been caught.
Pub Weekly, October 2012.
Booklist, September 2012.
Horn Book, September 2012.
Kirkus Review, September 2012.
Pub Weekly.
Booklist.
Keywords: Trout -- Juvenile fiction; Fishes -- Juvenile fiction; Storytelling -- Juvenile fiction; Tall tales; Trout -- Fiction; Fishes -- Fiction; Storytelling -- Fiction; Tall tales; Trout -- Fiction; Fishes -- Fiction; Storytelling -- Fiction; Tall tales; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Legends, Myths, Fables / Other; JUVENILE FICTION / Animals / Fishes; Trout -- Fiction; Fishes -- Fiction; Storytelling -- Fiction; Tall tales; Picture books for children